Non-invasive fecal microbiota transplantation for recurrent Clostridium difficile infection in a patient presenting with hypertensive disorder post interventionem - Goeser, F.; Schlabe, S.; Ruiner, C. E.; Kramer, L.; Strassburg, C. P.; Spengler, U. (Zeitschrift für Gastroenterologie, 2016)
Fecal microbiota transplantation has gathered much attention due to its high efficacy in resolving recurrent Clostridium difficile infection. Until today, it is recognized as a safe procedure without any severe side effects. Patients with impaired conscious states suffering from recurrent episodes of aspiration are at increased risk by endoscopic interventions needed during standard approaches for fecal microbiota transplantation application.Here, we illustrate the case of a tetraplegic patient undergoing fecal microbiota transplantation due to his fifth recurrent episode of Clostridium difficile infection using a self-advancing nasal jejunal feeding tube as effective minimal-invasive option of fecal microbiota transplantation application. Persistent aggravation of arterial hypertension, which developed post-intervention in this patient, could be interpreted as a hitherto unknown side effect of fecal microbiota transplantation in this setting. Moreover, this is a further hint for a link between the intestinal microbiome and arterial hypertension in general.
Keywords: Clostridium difficile Infektion; Fäkale Mikrobiota-Transplantation; Intestinales Mikrobiom; Arterielle Hypertension